Biochemical characterization of the flavedo of heat-treated Valencia orange during postharvest cold storage - Perotti, Valeria Elisa (2015)
Heat treatment is a powerful and eco-friendly method to prevent Penicillium infection in citrus fruit during the postharvest. Several studies have been dedicated to investigate the general chemical changes that justify the immediate reaction responsible for the induced tolerance; but just how primary metabolism and enzymology are affected by heat treatment and along a prolonged cold storage is still unclear. In this work, the main enzymes of carbon metabolism of Valencia orange flavedo were analyzed during the postharvest period after a heat treatment (HT) of 48 h at 37 °C. Enzymatic activity measurements indicated that the NADPH producing enzymes glucose 6-phosphate dehydrogenase and non-phosphorylating glyceraldehyde 3-phosphate dehydrogenase have lower levels in HT fruit. In parallel, a higher synthesis of sucrose from organic acids was observed in HT epicarp. Sucrose-phosphate synthase would have an important role in sucrose accumulation. The pathway of carbon through glycolysis was affected by cold storage, independently of HT, in a way that it favors the ATP-dependent phosphofructokinase over the PPi-dependent homologous enzyme and the use of phosphoenolpyruvate (PEP) by PEP carboxylase instead of pyruvate kinase. Similarly, phenylpropanoid compounds did not show major changes in response to HT, although some of them showed a marked descent along the cold storage. Proteomic studies revealed alterations in the abundance of ascorbate peroxidase, two germin-like proteins and small HSPs, completing the description of the main metabolic changes in this tissue.